A BIBLIOMETRIC ANALYSIS OF CARBON TAX LITERATURE: FUTURE RESEARCH FOR INDONESIA - Ghea Revina Wigantini; Yunieta Anny Nainggolan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In recent years, the carbon tax has become a popular discussion among countries. After careful consideration, Indonesia plans to implement carbon tax policies in 2022. As a result, there will be beneficial and on the other hand, negative influences. As a new player in implementing carbon tax policies, Indonesia could learn from the country that implemented it first. Using bibliometric analysis, this study is expected to give insight to the next researcher and concerned party for the future research direction on carbon tax policy and its impact on the related parties. This research assesses the most prolific authors, source institutions, and nations, as well as the most cited papers and the most popular keywords using the Scopus database. Indonesia has a big chance to do research related to the carbon tax. We recommend that Indonesian scholars focus on the economic and business level in their future research related to the carbon tax.